Scientific Integration of Pesantren and Science: Pesantren's Contribution to the Development of Science and Technology - Muhammad Aldi; Retisfa Khairanis (Proceeding of International Conference on Islamic Boarding School, 2025)
This research aims to analyse how pesantren knowledge is integrated into the development of knowledge and technology and the contribution of pesantren to the development of science in Indonesia.  In the traditional Islamic education system, pesantren have an important role in developing a generation of intelligent Muslims who understand not only religious knowledge but also contemporary science and technology.  This research uses a qualitative approach using case study methodology on several santris that have incorporated science and technology into their curriculum.  Data were collected through interviews with kiai, santri, and pesantren staff as well as observations of the education system and facilities in the pesantren. The findings of this study show that some schools in Indonesia have successfully developed educational models based on the integration of Islam and science.  This implementation can be seen in STEM education based on Islamic principles, the development of science laboratories in pesantren, and collaboration with universities and research institutions in the development of local wisdom-based technology.  Pesantren also participate in the development of halal technology, such as the creation of new pharmaceutical, food, and energy products that comply with sharia principles. The implication of this study is that pesantren have significant potential to strengthen the Islamic education system based on innovation and research.  Pesantren contribute not only in the field of religion but also in the development of Muslim intellectuals who are competitive in the modern world.  The results of this study can be a reference for the parties involved in determining a more inclusive strategy for the development of pesantren education in relation to knowledge and technology.